Percepções de uma professora de Inglês sobre sua sala de aula: Uma visão êmica - Andrea Machado de Almeida Mattos (2000)
This study investigated a pre-service English teacher and her perceptions about her classroom from her own point of view. The research design was based on theoretical and empirical studies about classroom research and about the FL teacher, adopting an interpretivist and emic vision. The main objective of the research was to search for a global understanding of how the FL teacher interprets the events present in the classroom. To this end, a case study was conducted, using retrospective interviews as the main data collection instrument. The objective of these interviews was to foster the informants critical reflection on her performance inside the classroom to promote her professional development. The content of these interviews was categorized, leading to the expansion of Richards (1998) reflective categories. Next, quantitative and qualitative analyses were conducted. The results of the quantitative analysis led to a global view of the informants perceptions of her classroom. The qualitative analysis provided a better understanding of the factors that influence a FL teachers daily life and evidence of the existence of two levels of action in the classroom culture. The analysis also revealed that the data collection methodology favored the informants critical reflection, fostering her professional development. Based on the research findings, Wallaces (1991) model for FL teacher education was modified. The results of this study bring implications to the field of FL teacher education and to the relationship between the researcher and the participant-teacher.